2020
DOI: 10.3390/cells9071659
|View full text |Cite
|
Sign up to set email alerts
|

“The Social Network” and Muscular Dystrophies: The Lesson Learnt about the Niche Environment as a Target for Therapeutic Strategies

Abstract: The muscle stem cells niche is essential in neuromuscular disorders. Muscle injury and myofiber death are the main triggers of muscle regeneration via satellite cell activation. However, in degenerative diseases such as muscular dystrophy, regeneration still keep elusive. In these pathologies, stem cell loss occurs over time, and missing signals limiting damaged tissue from activating the regenerative process can be envisaged. It is unclear what comes first: the lack of regeneration due to satellite ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 133 publications
(186 reference statements)
0
23
0
1
Order By: Relevance
“…These include immune cells and fibroblasts which play critical roles in all the stages of muscle repair [51]. Figure 2 summarises the relationship between the different cell type influencing muscle growth and repair in inflammatory conditions such as rheumatoid arthritis [34,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Satellite Cell Activation and Cell-cell Cross-talk In Responmentioning
confidence: 99%
“…These include immune cells and fibroblasts which play critical roles in all the stages of muscle repair [51]. Figure 2 summarises the relationship between the different cell type influencing muscle growth and repair in inflammatory conditions such as rheumatoid arthritis [34,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Satellite Cell Activation and Cell-cell Cross-talk In Responmentioning
confidence: 99%
“…The process of muscle fibrosis in patients with muscular dystrophies is highly complex and not completely understood (34). It is known that chronic muscle degeneration leads to persistent inflammatory infiltration, muscle necrosis and activation of fibroadipogenic progenitor cells (FAPs) and fibroblasts, which release proteins of the extracellular matrix such as collagen-I, leading to the expansion of fibrotic tissue (34)(35)(36). The PDGF family in general and PDGF-AA in particular play an important role in this process (22, 37).…”
Section: Discussionmentioning
confidence: 99%
“…While most of these strategies are obviously focused on muscle cells, which bear the genetic defect, it is now clear in the field that we should also take into account the cellular environment. Indeed, several studies demonstrated the importance of non-muscle cells in the progression of MDs, particularly MPs 28,[40][41][42][43] . In this study, we demonstrated that the expression of transcription factor Nfix induces pro-fibrotic features in MPs in a context of chronic muscle injury.…”
Section: Discussionmentioning
confidence: 99%